1996
DOI: 10.1128/mcb.16.5.1946
|View full text |Cite
|
Sign up to set email alerts
|

Shc Proteins Are Localized on Endoplasmic Reticulum Membranes and Are Redistributed after Tyrosine Kinase Receptor Activation

Abstract: The intracellular localization of Shc proteins was analyzed by immunofluorescence and immunoelectron microscopy in normal cells and cells expressing the epidermal growth factor receptor or the EGFR/erbB2 chimera. In unstimulated cells, the immunolabeling was localized in the central perinuclear area of the cell and mostly associated with the cytosolic side of rough endoplasmic reticulum membranes. Upon epidermal growth factor treatment and receptor tyrosine kinase activation, the immunolabeling became peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 44 publications
6
58
0
Order By: Relevance
“…This growth factor-induced association of Shc with the cytoskeleton suggests a role for Shc in membrane ruffling and actin fiber reorganization. Shc appears to be also involved in endocytosis, as it is recruited to endocytic structures such as coated pits and endosomes in response to growth factor receptor stimulation (Lotti et al, 1996). This potential role is supported by the finding of an interaction of Shc, mediated by the CH1 domain, with ␣-and ␤-adaptin components of plasma membrane adaptor proteins that are believed to be involved in receptor endocytosis (Obayashi et al, 1996).…”
Section: Shc In Alternative Signaling Pathwaysmentioning
confidence: 53%
“…This growth factor-induced association of Shc with the cytoskeleton suggests a role for Shc in membrane ruffling and actin fiber reorganization. Shc appears to be also involved in endocytosis, as it is recruited to endocytic structures such as coated pits and endosomes in response to growth factor receptor stimulation (Lotti et al, 1996). This potential role is supported by the finding of an interaction of Shc, mediated by the CH1 domain, with ␣-and ␤-adaptin components of plasma membrane adaptor proteins that are believed to be involved in receptor endocytosis (Obayashi et al, 1996).…”
Section: Shc In Alternative Signaling Pathwaysmentioning
confidence: 53%
“…Lotti et al (1996) also observed that Shc proteins are localized to the membranes by immuno¯uorescence. When di erent domains of Shc were transiently expressed in COS cells, the PTB domain of Shc was su cient for localization to the membrane fractions .…”
Section: Shc ± Ptb Domainmentioning
confidence: 76%
“…To address this, we investigated whether the precursor forms of RetD6 and Ret2A were able to bind the Shc adapter protein. This protein is localized to the membrane of the rough endoplasmic reticulum and has been previously demonstrated to bind Ret/ PTCs, Ret2A and Ret2B (a mutant Ret receptor carrying an M918T mutation) oncoproteins (Lotti et al, 1996). Cell lysates from RetD6 and Ret2A transfected NIH3T3 cells were immunoprecipitated with anti-Shc or anti-Ret antibodies and subsequently blotted with anti-Ptyr antibodies (Figure 3).…”
Section: Biosynthesis and Glycan Processing Of Retd6 And Ret2a Proteimentioning
confidence: 99%